2019
DOI: 10.5267/j.uscm.2018.11.001
|View full text |Cite
|
Sign up to set email alerts
|

The mediating role of technology and logistic integration in the relationship between supply chain capability and supply chain operational performance

Abstract: The purpose of this paper is to explore the link between supply chain capability and supply chain operational performance. In addition, the current study investigates the mediating role of technology integration and logistic integration between supply chain capability and supply chain operational performance. The firms in Tin industry of Indonesia are chosen as the sample of the study. To achieve the objectives of the current study, structural equation modeling is used using smart PLS. Data is collected throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 58 publications
1
17
0
1
Order By: Relevance
“…Likewise, the research has also revealed that size and transformational leadership had a statistically significant regulatory role in the relationships between SCMP and SCI as well as between SCMP and SCP. This results are consistent with the research of Naway and Rahmat (2019). Vietnamese textile and garment enterprises should attach special importance to SCMP activities towards SCI and SCP as recommended in the research by Daehy et al (2019).…”
Section: Research Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Likewise, the research has also revealed that size and transformational leadership had a statistically significant regulatory role in the relationships between SCMP and SCI as well as between SCMP and SCP. This results are consistent with the research of Naway and Rahmat (2019). Vietnamese textile and garment enterprises should attach special importance to SCMP activities towards SCI and SCP as recommended in the research by Daehy et al (2019).…”
Section: Research Resultssupporting
confidence: 90%
“…The research is to evaluate SCI's intermediary role in the relationship between SCMP and SCP. Previous studies have shown that SCI has a partial intermediary role in the relationship between SCMP and SCP when surveying 156 electronics companies in Malaysia in the studies by Sundram et al (2015), Naway and Rahmat (2019). Enterprises implement a set of supply chain management activities to promote collaboration between internal departments and cooperate with other companies from suppliers to customers in the supply chain (Pramatari, 2007).…”
Section: Literature Review and Research Hypothesesmentioning
confidence: 99%
“…The mutual influence of operating activities, integration processes and logistics are considered in [20]. At the same time, the authors note that the most significant is the exchange of information to improve the efficiency of the entire supply chain.…”
Section: The Principles Of Building Logistics Platforms Includementioning
confidence: 99%
“…Factors such as provision of order & product arrival information, online payment security, chat room functions, easy to operate search engines, comparison, complete information about the product etc. determines the success of online market (Omar et al, 2011;Naway & Rahmat, 2019).…”
Section: Review Of Literaturementioning
confidence: 99%